The complete mitochondrial genome of the Xinyuan honey bee, Apis mellifera sinisxinyuan (Insecta: Hymenoptera: Apidae). Issue 1 (2nd January 2020) - Yang, Jialin; Jiao, Ziwei; Wen, Xuemei; Liu, Bei; Huang, Jiaxing; Ding, Guiling
Abstract: We analyzed the complete mitochondrial genome of the recently discovered Xinyuan honey bee, Apis mellifera sinisxinyuan using single molecule real-time sequencing. The mitochondrial genome of A. m. sinisxinyuan is a circular molecule of 16, 886 bp, comprising 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and a control region rich in A + T. Phylogenetic analysis using 13 protein-coding genes supports a close relationship to another M-lineage honey bee, A. m. mellifera .